Synthesis, Spectroscopic Characterization, and DFT Study of (E)-N-((1-(4-fluorophenyl)-1H-pyrazol-4-yl) methylene)-2-(1H-indol-3-yl) ethanimine - Sapkota, Kamal Raj; Anand, Vaishali; Rai, H.C. (Kanya Journal, 2025)
A new Schiff base compound, (E)-N-((1-(4-fluorophenyl)-1H-pyrazol-4-yl)methylene)-2-(1H-indol-3-yl)ethanimine (FME), was created by reacting 1-(4-fluorophenyl)-1H-pyrazole-4-carbaldehyde with 2-(1H-indol-3-yl)ethan-1-amine under condensation conditions. The molecular structure was verified using elemental analysis and a suite of spectroscopic tools, including NMR, FT-IR, UV-Vis, and mass spectrometry. Both ^1H and ^13C NMR spectra confirmed the presence of the imine bond and aromatic rings, while FT-IR and UV-Vis spectra highlighted the formation of the Schiff base and extensive π-conjugation. The mass spectrum showed a molecular ion peak at m/z 332.14, consistent with the predicted molecular weight. Frontier Molecular Orbital (FMO) analysis revealed a HOMO–LUMO energy gap of 3.951 eV, indicating stable electronic properties and potential for charge transfer. Together, these analyses confirm that FME was successfully synthesized and structurally intact, supporting its potential for exploration in materials science and biological studies.